2001
DOI: 10.1542/peds.107.6.1241
|View full text |Cite
|
Sign up to set email alerts
|

Fever Phobia Revisited: Have Parental Misconceptions About Fever Changed in 20 Years?

Abstract: Fever phobia persists. Pediatric health care providers have a unique opportunity to make an impact on parental understanding of fever and its role in illness. Future studies are needed to evaluate educational interventions and to identify the types of medical care practices that foster fever phobia.fever, fever phobia, child, children, antipyretics, sponging, health care practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
493
9
62

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(590 citation statements)
references
References 15 publications
26
493
9
62
Order By: Relevance
“…A recent study concluded that health care providers are in a unique position to educate parents with regard to fever, 17 and our data suggest that physicians, family members and nurses are the most common source of information about fever. Our data also suggest that books and magazines are increasingly important information sources.…”
Section: Information Sourcesmentioning
confidence: 50%
“…A recent study concluded that health care providers are in a unique position to educate parents with regard to fever, 17 and our data suggest that physicians, family members and nurses are the most common source of information about fever. Our data also suggest that books and magazines are increasingly important information sources.…”
Section: Information Sourcesmentioning
confidence: 50%
“…These findings were similar to that of Crocetti M et al, as 85 per cent of parents (340) reported awakening their child from sleep to give antipyretics and forty-three per cent (264) of the mothers, indicated that they administer antipyretics without measuring their children's temperatures. 10 Parents should know that clinical research tested this observation. It was found that experienced mothers were wrong in 50 per cent of the time in diagnosing low-grade fevers (38.3-38.9°C) by touch.…”
Section: Resultsmentioning
confidence: 99%
“…10,17 It contained 25 items to evaluate the parent's knowledge about their children's fever, and their beliefs towards it. The Items also were chosen to explore their patterns of use of OTC antipyretics and temperature management practices.…”
Section: Questionnaire Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The fever accounts for about a third of the children's medical visits [1]. Fever also has positive effects; it both alarms for infections or inflammation in the body, and stimulates the immune system and prevents the growth of certain bacteria.…”
Section: Introductionmentioning
confidence: 99%